Stock Prices Volatility as an Input to the Economic Assessment of the Nuclear Power Plant in the Real Option Method - Krysiak, Zbigniew (Copernican Journal of Finance & Accounting, 2025)
The aim of the study was to determine the impact of the share in the activities of the companies for the nuclear sector on the volatility of their stock prices. Activities of the companies in the nuclear sector are measured by value of produced nuclear assets (NUA) build in the nuclear power plants (NPP). If the impact of produced NUA on stock’s volatility would be found then it may be used as a good measure of asset volatility when assessing the efficiency of nuclear power plant projects using the real options method supported by Monte Carlo simulation. The presented study covered 23 types of assets, including 10 ETF funds and 13 companies listed on various stock exchanges in the world, which operate in the nuclear sector. ETF funds usually have in their portfolios from several to a dozen or so different company assets, which means that the study actually covered approx. 150 entities involved in the provision of products and services for nuclear power plants and simultaneous production of heat and electricity based on nuclear energy. Regression analysis showed a strong correlation between volatility of stock prices and share in NUA production for ETF funds at the level of with p-Value below 0.01. For the companies traded on the stock exchange, this relationship was very strong at the level of with p-Value also below 0.01. The studied sample is considered to be representative since reflects a significant part of the nuclear sector. From 10% to 100% of the production and services of the studied entities are directed to the nuclear sector. Patterns of the volatility distributions were prepared to be used as an input variable for modeling the distribution of the option values and the value of a nuclear power plant, and also level of risk. The final conclusion was that the growing share of companies' activities in the nuclear sector increases the standard deviation of return rates, which means that increasing risk will lead to attractive rates of return for the shareholders and stakeholders.